2021
DOI: 10.36233/0372-9311-67
|View full text |Cite
|
Sign up to set email alerts
|

Association of the increased circulating CD62LloCXCR4hi neutrophil count with carotid atherosclerosis

Abstract: Introduction. The role of neutrophils in the initiation and progression of atherosclerosis as well as in the development of its complications has received scientific attention only in the recent years. Today, there is growing evidence to support a role of the CXCL12/CXCR4 axis in sustained inflammation during different chronic inflammatory diseases by retaining neutrophils at inflammatory sites.The aim of the study is to assess the diagnostic and prognostic significance of circulating CD62LloCXCR4hi neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In a previous study conducted on a small mixed-sample of patients, we were able to establish the existence of relationships between an increase in the number of CD62L lo CXCR4 hi -neutrophils and the extent of carotid atherosclerosis [ 36 ]. The present study has served to significantly expand on the previously obtained data with regard to the diagnostic value of aging neutrophils in relation to subclinical polyvascular atherosclerosis in statin-naïve patients aged 40 to 64.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study conducted on a small mixed-sample of patients, we were able to establish the existence of relationships between an increase in the number of CD62L lo CXCR4 hi -neutrophils and the extent of carotid atherosclerosis [ 36 ]. The present study has served to significantly expand on the previously obtained data with regard to the diagnostic value of aging neutrophils in relation to subclinical polyvascular atherosclerosis in statin-naïve patients aged 40 to 64.…”
Section: Discussionmentioning
confidence: 99%
“…The cervix increases pro-inflammatory cytokine production to help fight off infection. Pregnant women with bacterial vaginosis or cervicitis have higher levels of IL-1β, IL-6, and IL-8 in their cervical mucus compared to patients with normal pregnancies ( 98 100 ). Bacterial and viral infections can also elicit a type 1 T-helper lymphocyte response in the cervix.…”
Section: Endogenous Defense Mechanisms Of the Cervix Against Infections During Pregnancymentioning
confidence: 99%
“…The type of cervical infection and the specific cellular and immunologic responses of the cervix against infections can be used as biomarkers for diagnosing infections and prognosticating pregnancy outcomes ( 98 , 100 ). Previous studies have shown some potential biomarkers associated with cervical infections that may be useful in predicting adverse pregnancy outcomes.…”
Section: Potential Cervical Biomarkers Of Adverse Pregnancy Outcomesmentioning
confidence: 99%